A Specific PfEMP1 Is Expressed in P. falciparum Sporozoites and Plays a Role in Hepatocyte Infection - Zanghì, Gigliola; Vembar, Shruthi S.; Baumgarten, Sebastian; Ding, Shuai; Guizetti, Julien; Bryant, Jessica M.; Mattei, Denise; Jensen, Anja T.R.; Rénia, Laurent; Goh, Yun Shan; Sauerwein, Robert; Hermsen, Cornelus C.; et al. (Cell reports (Cambridge), 2018)
Heterochromatin plays a central role in the process of immune evasion, pathogenesis, and transmission of the malaria parasite Plasmodium falciparum during blood stage infection. Here, we use ChIP sequencing to demonstrate that sporozoites from mosquito salivary glands expand heterochromatin at subtelomeric regions to silence blood-stage-specific genes. Our data also revealed that heterochromatin enrichment is predictive of the transcription status of clonally variant genes members that mediate cytoadhesion in blood stage parasites. A specific member (here called NF54varsporo) of the var gene family remains euchromatic, and the resultant PfEMP1 (NF54_SpzPfEMP1) is expressed at the sporozoite surface. NF54_SpzPfEMP1-specific antibodies efficiently block hepatocyte infection in a strain-specific manner. Furthermore, human volunteers immunized with infective sporozoites developed antibodies against NF54_SpzPfEMP1. Overall, we show that the epigenetic signature of var genes is reset in mosquito stages. Moreover, the identification of a strain-specific sporozoite PfEMP1 is highly relevant for vaccine design based on sporozoites. [Display omitted] •Sporozoites expand subtelomeric heterochromatin to silence blood-stage-specific genes•A strain-specific PfEMP1 is expressed on the surface of sporozoites•NF54_SpzPfEMP1 is immunogenic in sporozoite-infected human volunteers•Antibodies against NF54_SpzPfEMP1 block sporozoite infection of hepatocytes P. falciparum PfEMP1 surface adhesion proteins mediate immune evasion and pathogenesis during asexual blood stage development. Zanghì et al. find that a strain-specific member of PfEMP1 is expressed at the sporozoite surface. Antibodies against this protein inhibit sporozoite invasion of hepatocytes in a strain-specific manner.